ERICACEAE OF LATIMOJONG RANGE, SOUTH SULAWESI - Abdulrokhman Kartonegoro (Floribunda, 2014)
The family of Ericaceae in Sulawesi is represented by four genera namely Diplycosia Blume, Gaultheria L., Rhododendron L. and Vaccinium L. The inventory number of species family Ericaceae in Latimojong Range was conducted based on field collections and herbarium study in Herbarium Bogoriense. Thirty species and two varieties are recognized consist of 4 of Diplycosia, 3 of Gaultheria, 19 of Rhododendron and 6 of Vaccinium. Twenty seven species and two variety are endemic to Sulawesi while 17 of it endemic for Latimojong Range. High endemicity of species Ericaceae in Latimojong Range will need more concern and protection as a conservation site.